Acute panuveitis and Takayasu's arteritis. Issue 10 (19th September 2003) - Kausman, J Y; Walker, A; Piper, S
Abstract : A 12 year old boy presented with severe hypertension and was diagnosed with renal artery stenosis requiring balloon angioplasty. Takayasu's arteritis was subsequently diagnosed, but he also developed acute panuveitis, an entity not previously reported in a child with this condition.